Proof of Concept utveckling av dataanalyseringsverktyg – för teknologievaluering av smarta hem lösningar - Phu, Marcus (My University, 2023)
Due to the issues of rising electricity costs in Sweden and households having trouble paying their electrical bills this project aims to develop a tool that enables the household to evaluate what the effect of using a smart home solution have on their electrical expenses. The project was conducted in collaboration with Njord Engineering, a consulting firm, and their client, an energy company. To evaluate the impact of smart home solutions on electricity costs, a Proof-of-Concept data analysis tool was developed. The tool, a web application designed for PC, enables users to compare their electricity costs under different pricing models, including fixed-rate, variable-rate, and smart home-assisted pricing. By analyzing real-time data obtained from an electricity exchange, the tool provides insights into the financial implications of adopting smart home technologies. A survey was conducted during the project to gather society’s opinions on smart home products and their control preferences. This data was used to develop an algorithm for simulating smart home solution usage. Additionally, an analysis was performed on the simulations to assess the tool’s potential in helping households determine the impact of smart home solutions on electricity costs. The analysis involved comparing electricity costs under different rates with the costs associated with using a smart home solution. The results of the project include a functional data analysis tool and simulation algorithm for smart home solution usage. The analysis of simulations conducted by the tool is also presented. The project’s conclusion is that the developed tool successfully achieved its goals, demonstrating its potential to help users evaluate the impact of smart home solutions on their electricity costs. Although the analysis results are not realistic due to the dataset limitations, they highlight the tool’s potential to prove the concept of reducing household electrical costs with smart home solutions.
Keywords: Webbapplikation; React.js; TypeScript; Smart home; Electric prices; Agile